Antibody Therapy Substitution - Immunomodulation - Monoclonal Immunotherapy (Springer International Publishing, 2018)
This practical manual, written by well-known experts, reviews current indications for the use of IgG concentrates and some other modern immunomodulators and provides fundamental information on present-day immunomodulation in patients (and mice). The book opens by tracing the transition from IgG substitution to IgG immunomodulation and providing expert updates on immunomodulatory indications in autoimmune and inflammatory disorders, including hematologic, neurologic, dermatologic, and other diseases. Basic aspects of IgG concentrates, including methods of production, safety, currently available products, and mechanisms of action, are then discussed. An entire chapter is devoted to the different aspects of immunomodulatory IgG treatment in the bleeding disorder immune thrombocytopenia (ITP). Finally, the transition from polyclonal to monoclonal antibody (mAb) treatment is addressed in detail, covering mAb development, methods, mechanisms of action, adverse effects, and more. Particular attention is paid to the example of anti-CD20 (B-cell) antibody.